Shift from visceral to subcutaneous adipose tissue in Cyp17a1-knockout rats prevents the progression of metabolic syndrome - Beom-Jin Jeon; Jeong-Hwa Lee; Dong-Hyeok Kwon; Hee-Kyoung Kim; Goo Jang (PLoS ONE, 2025)
In this study, we investigated the effects of Cyp17a1 gene knockout (KO) on obesity and metabolic syndrome. Cyp17a1 KO in rats using CRISPR-Cas9 resulted in sex dimorphism and obesity, and interestingly, site-specific accumulation was found in subcutaneous adipose tissue (SAT). Surprisingly, an insulin tolerance test and oral glucose tolerance test did not show any issues with insulin sensitivity and secretion despite hyperglycemia. In addition, Cyp17a1 KO rats showed normal plasma insulin and free fatty acid levels compared to wild-type rats, and blood biochemistry analysis revealed normal triglyceride, total cholesterol, high-density lipoprotein, and low-density lipoprotein levels. Cyp17a1 KO adipose-tissue-derived stem cells from SAT showed increased expression of KLF5, an early adipogenesis marker, which implies enhanced adipogenic potential in SAT. When gene expression associated with lipid, glucose, and insulin metabolism as well as inflammation in adipose tissue was examined, a metabolic shift to SAT was discovered in the Cyp17a1 KO group. In conclusion, in the Cyp17a1 KO rat models we generated for the first time, the phenotype promoted by obesity reflected metabolically healthy obesity hypothesis, but this did not exhibit metabolic syndrome-like features due to enhanced metabolism in the SAT.